Integration against the state: Irregular migrants' agency between deportation and regularisation in the United Kingdom. (August 2017) - Schweitzer, Reinhard
Reducing the number of foreigners residing unlawfully within the borders of a state requires either their removal or the legalisation of their presence within the territory. Increasingly, governments also employ measures of internal control and limit irregular migrants' access to rights and services in order to encourage them to leave autonomously. This article aims to contribute to current debates on how to conceptualise and account for the agency that irregular migrants themselves exercise in such contexts. Within critical migration and citizenship studies, many of their everyday actions have been described as 'acts of citizenship' but also as instances of 'becoming imperceptible', neither of which captures the whole range of strategies irregular migrants employ to strengthen their fragile position vis-à-vis the state. I argue that conceptualising their agency in terms of (self-)integration allows us to account for both: practices through which they actively become political subjects as well as those that precisely constitute a deliberate refusal to do so. Empirically, this is underpinned by an analysis of recent policy developments in the United Kingdom and a series of semi-structured interviews I conducted during 8 months of fieldwork in London with migrants experiencing different kinds and degrees of irregularity.